BASAVARAJ KATTIMANI’S NOVEL ON THE VOLCANO CLASS CONFLICT IN THE NOVEL - Bharati sangappa Gaddi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
On the volcano is a renowned work of progressive literature. A work that captures the exploitation of labor, the background of the protest - its birth, its quantitative growth, the dynamic form of the conflict as much as possible. The way in which the Congressman Chandranna, who was a Gandhian, transformed into a communist is also the development of the conflict. Class conflict is not an individual action and protest but has to emerge in its own law. Its background, foreground, and dynamics are all written in the structure here. Even after independence, the majority of Hindustan did not get economic ’freedom’. Their legacy of hardship is not gone. He (Chandranna) believed that the goal of the Congress was to establish a state of farmers and laborers. He had decided that he would work with the workers to achieve that goal. But when he saw the group of selfish people who had recently joined the Congress organization, he was not without suspicion. Profit-seeking traders, black marketeers, miserly people who preyed on the poor for money, and unworthy people who were greedy for power, were infiltrating the Congress organization in droves. The Congress, which was supposed to be a refuge for the poor, was becoming a haven for thieves and robbers’ (page 53). This is the atmosphere of the rulers.